2017
DOI: 10.1186/s12995-017-0177-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of lymphoma subtypes by occupational exposure in Southern Italy

Abstract: BackgroundOccupational exposure is known to play a role in the aetiology of lymphomas. The aim of the present work was to explore the occupational risk of the major B-cell lymphoma subtypes using a case–control study design.MethodsFrom 2009 to 2014, we recruited 158 lymphoma cases and 76 controls in the provinces of Bari and Taranto (Apulia, Southern Italy). A retrospective assessment of occupational exposure based on complete work histories and the Carcinogen Exposure (CAREX) job-exposure matrix was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
0
23
0
6
Order By: Relevance
“…In the study of Ferri et al, no statistical significance was found between the risk of lymphoma and 22 chemical products. Increased risk was detected for all lymphomas in cases exposed to captafol, exposed to low paraquat levels and moderate radon levels [23].…”
Section: Results Obtainedmentioning
confidence: 93%
See 2 more Smart Citations
“…In the study of Ferri et al, no statistical significance was found between the risk of lymphoma and 22 chemical products. Increased risk was detected for all lymphomas in cases exposed to captafol, exposed to low paraquat levels and moderate radon levels [23].…”
Section: Results Obtainedmentioning
confidence: 93%
“…The participants in the case-control group were usually selected from the existing hospital/health records or from the results of prospective cohort studies. It was determined that the minimum and maximum numbers of samples were 158 [23] and 1690 [24], respectively.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…4-11.8) [27]. Several other studies found no association between HL and pesticide use [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, causes and effects are well known: the starting point is the overuse of a certain part of the body, to which many factors may contribute, and results are well-identified illnesses, such as tendonitis and bursitis. But what happens between the two phases, is not very clear and, in many cases, is strongly IJIEM affected by individual's biological response [1]. According to the Agency for Safety and Health at Work [2], in the European Union, the work musculoskeletal disorders (WMSDs) are costing 3.3% of GDP, which implies an annual cost of €476 billions and around 7 million of disability-adjusted life years (DALYs).…”
Section: Introductionmentioning
confidence: 99%